2009
DOI: 10.1134/s0006297909120050
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal fragment of human laminin-binding protein contains a receptor domain for Venezuelan equine encephalitis and tick-borne encephalitis viruses

Abstract: Polyclonal and monoclonal antibodies (MABs) to human laminin-binding protein (LBP) can efficiently block the penetration of some alpha- and flaviviruses into the cell. A panel of 13 types of MABs to human recombinant LBP was used for more detailed study of the mechanism of this process. Competitive analysis has shown that MABs to LBP can be divided into six different competition groups. MABs 4F6 and 8E4 classified under competition groups 3 and 4 can inhibit the replication of Venezuelan equine encephalitis vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 33 publications
1
34
1
Order By: Relevance
“…The ED3 domain from YFV interacted mainly with the acid C-domain of RPSA whereas the ED3 domain from WNV interacted only with its N-domain. As regards alphaviruses, it has been reported that the C-domain of RPSA includes a binding site for VEEV and that its N-domain includes a binding site for SINV [9,26]. Therefore our results and previous data indicate that both N- and C-domains of RPSA could serve as viral receptors.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The ED3 domain from YFV interacted mainly with the acid C-domain of RPSA whereas the ED3 domain from WNV interacted only with its N-domain. As regards alphaviruses, it has been reported that the C-domain of RPSA includes a binding site for VEEV and that its N-domain includes a binding site for SINV [9,26]. Therefore our results and previous data indicate that both N- and C-domains of RPSA could serve as viral receptors.…”
Section: Discussionsupporting
confidence: 74%
“…In particular, human RPSA is a potential cellular receptor for several flaviviruses, including DENV (dengue virus) and TBEV (tick-borne encephalitis virus) [19,20,24,25], and for several alphaviruses including VEEV (Venezualian equine encephalitis virus) and SINV (Sindbis virus) [9,18,26]. The envelope protein of flaviviruses includes three ectodomains, ED1, ED2 and ED3 and a transmembrane region.…”
Section: Introductionmentioning
confidence: 99%
“…Of these proteins, E2 is responsible for receptor binding and E1 facilitates the low-pH-dependent membrane fusion process (8,9). Multiple receptors that facilitate SFV, SINV, RRV, and VEEV cell entry have been identified, but none of these receptors appear to be crucial (10)(11)(12)(13)(14)(15)(16). The receptors identified act predominantly as attachment factors to capture the virus.…”
mentioning
confidence: 99%
“…Recombinant LBP has been produced and purified by metal‐chelate chromatography as discussed by us before (Sorokin et al ., ). mAbs to LBP and TBEV protein E have been produced as discussed by us before (Protopopova et al ., ; Malygin et al ., ). The Е 257–415 and E 1–254 polypeptides and protein E of TBEV were detected by means of the IEA with mAbs 10H10 against protein E of TBEV for capturing viral antigens on the surface of 96‐well polystyrene plates.…”
Section: Methodsmentioning
confidence: 97%
“…These demonstrations enabled us to propose and then to experimentally confirm the existence of an additional and different receptor region for the case of WNV protein E, the region located in the domain II of this protein and very close or identical to the location of the fusion peptide (Morozova et al ., ). Specificity of the corresponding interaction with LBP has been also confirmed by the mapping of an interaction site using a C‐end LBP fragment (Malygin et al ., ). Note that LBP is exploited as a cell receptor also by dengue, Sindbis and Venezuelan equine encephalitis viruses (Strauss et al ., ; Ludwig et al ., ; Bondarenko et al ., ).…”
Section: Introductionmentioning
confidence: 98%